BETWEEN DIGITAL RESPONSES AND EXPERIENTIAL KNOWLEDGE: CHATGPT AND EDUCATION FROM A CRITICAL PERSPECTIVE - Barbosa, Roberta de Oliveira [UNESP]; Taveira, Flávio Augusto Leite [UNESP]; Peralta, Deise Aparecida [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2024)
Digital advances are reshaping education by expanding access to online resources and generating reflections on their impact in contemporary society. The growing use of Artificial Intelligence (AI)—such as ChatGPT—in education brings efficiency, but incurs ethical dilemmas. This article explores to what extent this tool can replace human memory and experience by analyzing identical interviews conducted with a human teacher and ChatGPT, using eight structured questions for comparison. Analysis of the answers, carried out using IRaMUTeQ software, reveals differences in lexical distribution and thematic focus. The results show that ChatGPT does not replace human experience, highlighting differences in language and thematic emphasis between the human teacher and the AI. This study underscores the need for a critical examination of the relationship between humans and technology in qualitative research and highlights the importance of an ethical approach to using these tools.
ENTRE RESPOSTAS DIGITAIS E SABERES EXPERIENCIAIS: O CHATGPT E A EDUCAÇÃO EM PERSPECTIVA CRÍTICA
Keywords: Artificial Intelligence; Critical Theory; Memory; Teacher Education; Technology